Liquid Chromatography Mass Spectrometry Study of a Eutectic Mixture of bis(2, 2‐Dinitropropyl) Acetal/Formal. Issue 12 (20th October 2021) - Wong, Camille Hing; Edgar, Alexander Steven; Yang, Dali
Abstract: This study is the first attempt to document methodology development undergone using liquid chromatography tandem quadrupole time of flight mass spectrometry (LC‐QTOF) to investigate degradation products of eutectic bis(2, 2‐dinitropropyl) acetal/formal nitroplasticizer (called NP here). Method properties investigated are: desolvation temperature (°C) and spray voltage (V) of the electrospray ionization source, and the development of an acetone system rinse to prevent any residual contamination between sample injections. Details are given on why it is essential to investigate method optimization with changes shown in MS/MS analysis in addition to MS results. Trends in MS/MS analytic results reveal important relationships between baseline and aged materials. In addition to verification of previously proposed fragments, insights offered by this newly developed methodology will also identify new degradation products and shed light on the complexity of NP degradation chemistry. Abstract :